Reviewers and Forms - Reviewers and Forms (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2014)
AcknowledgementsThe articles in the present issue have undergone meticulous review by the following reputable experts:1. Prof. Sofendi, Ph,D., Universitas Negeri Sriwijaya, Palembang2. Dr. Rita Inderawati, M.Pd., Universitas Negeri Sriwijaya, Palembang3. Prof. Dr. Indawan Syahri, M.Pd., Universitas Muhammadiyah, Palembang4. Dr. Sunda Ariana,  M.Pd., M.M.,  Universitas Bina Darma, Palembang5. Dr. Dian Ekawati, M.Pd., Lembaga Penjamin Mutu Pendidikan, Palembang6. Dr. A. Gumawang Jati, M.A., Institut Teknologi Bandung, Bandung7. Dr. Yuli Utanto, M.Si., Universitas Negeri Semarang, Semarang8. Dr. Een  Y. Haenilah, Universitas Negeri Lampung, Lampung9. Dr. Nurlaelah, M.Hum., Universitas Muslim Indonesia, Makassar10. Drs. Deddy Suryana, M.A., Universitas Pendidikan Indonesia, Bandung11. Dr. Alimin Laundung, M.Pd., Politeknik Negeri Makassar, Makassar12. Drs. Zubaidi, Dipl. TESL, M.Pd., Politeknik Negeri Malang, Malang13. I Nyoman Rajin Aryana, S.Pd., M.Hum., Politeknik Negeri Bali, Bali14. Drs. Mulyadi, M.A., Universitas PGRI, Palembang15. Drs. Iman Suroso, M.Pd., Politeknik Negeri Semarang, Semarang             The Editor Board and Administrative Management of HOLISTICS Journal would like to extend their gratitude and appreciation to them for their scrupulous  work in reading and reviewing  the articles, and offering remarks and corrections for the betterment of the present issue. However, any possible deficiancy and negligence are the responsibility of the Journal Management.   HOLISTICS Journal Management